2005
DOI: 10.1002/pssb.200560970
|View full text |Cite
|
Sign up to set email alerts
|

Exciton‐polaritons and nanoscale cavities in photonic crystal slabs

Abstract: Recent theoretical work on exciton -light coupling in waveguide-embedded photonic crystals is reviewed. After a short description of the theory of photonic crystal slabs, the following issues are discussed: (i) a quantum-mechanical formulation of the interaction between photonic modes and quantum-well excitons, leading to a description of photonic crystal polaritons; (ii) calculations of variable-angle reflectance spectra, which show that radiative polaritons can be excited by an optical beam incident on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 52 publications
3
9
0
Order By: Relevance
“…From the full-width at half-maximum of our cavity peak (inset of figure 2a) we measure  c  = 160 μeV and  x  = 78 μeV for the single QD with some uncertainty attached to  γ x due to the limited resolution of our spectrometer. We usually have  c  >> γ x , besides for the vacuum Rabi , as similarly found for the L3 type cavity [16]. The Rabi splitting measured in this work is about 70 % of the 200 µeV predicted for Q = 8000.…”
supporting
confidence: 82%
“…From the full-width at half-maximum of our cavity peak (inset of figure 2a) we measure  c  = 160 μeV and  x  = 78 μeV for the single QD with some uncertainty attached to  γ x due to the limited resolution of our spectrometer. We usually have  c  >> γ x , besides for the vacuum Rabi , as similarly found for the L3 type cavity [16]. The Rabi splitting measured in this work is about 70 % of the 200 µeV predicted for Q = 8000.…”
supporting
confidence: 82%
“…It is out of the scope of the paper to perform a calculation of the QW electronic structure. This particular expression for describing the ground state of the exciton resonance of a QW (also known as 1 s exciton) has been employed successfully for describing the polariton dispersion in photonic crystals [14] and, very recently, by Liscidini et al in studying guided Bloch surface wave polaritons [15].…”
Section: A Model Detailsmentioning
confidence: 98%
“…We have adopted here a semi-classical approach, where the coupling between the QW and the PCM is accounted for implicitly by describing the fundamental exciton resonance as a Lorentzian medium (full details are presented in Section 2) [10][11][12][13][14][15]. The phenomenology to be presented responds to a dynamic or AC Stark effect, i.e., the effect of a rapidly varying field on a two-state system.…”
Section: Introductionmentioning
confidence: 99%
“…18 Shirane et al 17 reported a single defect or L1 nanocavities based on a triangular lattice GaAs photonic-crystal membrane with mode volume of V = 0.039 m 3 and a Q of17 000. The expressions for the probability amplitudes are strength involving a heavy hole electron, ⍀ 1/2 2 = ⌬ 2 +4g 1/2v,1/2c 2 with g 1/2v,1/2c being the coupling strength involving a light hole electron, with g 3/2v,1/2c = ͱ 3g 1/2v,1/2c , and ⌬ = − ph being the detuning frequency.…”
Section: A Designmentioning
confidence: 99%